A Methodology to Assess the Value of Integrated Hydropower and Wind Generation. Issue 3 (June 2014) - Clement, Mitch; Magee, Timothy; Zagona, Edith
Hydropower is considered a good resource to provide the needed flexibility to balance wind variability, but its flexibility is limited by non-power constraints associated with environmental and water management objectives not fully accounted for in previous wind integration studies. We present a method for a more realistic evaluation of integrated hydropower and wind using the RiverWare river system and hydropower modeling tool. The model provides a representation of physical and economic characteristics of the hydro system with the limitations from realistic non-power constraints. A test case is analyzed for a range of hydrologic conditions, levels of policy constraints and wind penetrations from 0 to 40 percent. Results show that at low penetrations wind adds economic value but has diminishing value as installed capacity increases, primarily due to increased reserve requirements. Increased wind generation increases policy constraint violations. Non-power constraints can significantly limit the total economic value of the integrated system.